A sensitive method for simultaneous determination of 12 classes of per- and polyfluoroalkyl substances (PFASs) in groundwater by ultrahigh performance liquid chromatography coupled with quadrupole orbitrap high resolution mass spectrometry. (July 2020) - Liu, Siqi; Junaid, Muhammad; Zhong, Wei; Zhu, Youchang; Xu, Nan
Abstract: Per- and polyfluoroalkyl substances (PFASs) comprise a large group of chemicals with diverse physicochemical properties, which make their simultaneous determination a challenging task. A trace analytical method based on ultrahigh performance liquid chromatography-quadrupole Orbitrap high resolution mass spectrometry (UHPLC-Q-Orbitrap HRMS) was developed for simultaneous determination of 54 PFASs belonging to 12 classes in groundwater, including 24 perfluorocarbons and 30 precursors. This method provided good linearity of calibration standards (R 2 > 0.99), excellent method limits of quantification (MLOQs) (0.5–250 pg/L), satisfactory matrix spiking recoveries (63%–148%), high precision (intra-day relative standard deviations (RSDs) 1.4–11.4%, inter-day RSDs 1.6–12.9%, and inter-week RSDs 2.1–12.7%), and short runtime (13 min), suitable for high throughput studies. The newly established method was successfully applied to detect PFASs in the groundwater samples collected from Hebei Province, China. Twenty PFASs were detected with the total concentration of 0.3–32.9 ng/L, indicating the contamination level similar to that in drinking water. The dominant PFASs were perfluorobutanesulfonate (PFBS), perfluorobutanoic acid (PFBA), perfluoropentanoic acid (PFPeA) and perfluorooctanoic acid (PFOA). In addition, 6:2 fluorotelomer phosphate diester (6:2 diPAP) and 6:2 fluorotelomer sulfonate (6:2 FTS) were found as the major precursors. The total PFAS concentrations were lower than the cumulative permissible limit of 70 ng/L for PFOS and PFOA recommended by the United States Environmental Protection Agency (USEPA) for drinking water in 2016. In a nutshell, this study provided a fast and sensitive method based on HRMS for the simultaneous analysis of a wide range of PFASs, present at trace levels in groundwater samples. Graphical abstract: Image 1 Highlights: A method was developed with Orbitrap HRMS for simultaneous analysis of 54 PFASs. The PFASs covered 12 classes, including 24 perfluocarbons and 30 precursors. The method achieved short runtime (13 min) and low MLOQs (0.5–250 pg/L). Twenty PFASs (0.3–32.9 ng/L) were detected in groundwater from Hebei Province. PFBS, PFBA, PFPeA, PFOS, 6:2 diPAP and 6:2 FTS were found as the major pollutants.